Modelagem de reservatórios de uso compartilhado para o controle de escoamento e aproveitamento de água pluvial - Schina, Bruno Álvaro (2022)
Urban expansion and disorderly occupation of city territories have caused several disasters associated with water systems. The main examples are floods that occur especially due to soil impermeability in natural infiltration areas. In search of sustainable solutions to control runoff, public policies encourage use compensatory techniques (TC) with the aim of mitigating urbanization impacts. A practice already used in Brazil and in other countries is runoff detention microreservoirs, whose premise is temporary storage volumes originated from impermeable areas runoff and drain out at a discharge lower than or close to pre-urbanization discharge. Another aspect of use reservoirs at origin of runoff is intended to fulfillment non-potable demands, through use Rainwater Reservoirs (RAAC). These have as a role inducing a decrease in potable water consumption for less noble purposes and preserving water sources. Some authors suggest classifying RAAC as a TC, since its function is to store rainwater. For this reason, some Brazilian cities are using RAAC to replace microreservoirs to control runoff at source (RCF). However, there is still a lack of conclusive studies that indicate with representativeness real benefits and impacts rainwater catchment and its use have on microdrainage networks. This study verified, based on a long-term simulation, the viability of using RAAC as reserve structures for use water and the effect of this mechanism on flow control at source. For this, the city of Curitiba was chosen, in a region of the Rebouças neighborhood with 415 buildings, and a 12-year local hourly precipitation series (2008 to 2019 – Station A807) was used for analyses. The RCF were dimensioned following Municipal Decree nº 1733/2021, which were submitted to simulations of observed precipitation to evaluate the number of infractions of these structures when subjected to real operating situations, in compliance with provisions in legislation. For same buildings and precipitation series, RAAC volumes necessary to fulfillment sanitary bowls demands were determined, with a minimum reliability of 80%, based on the simulation method and following good engineering practices as stated in NBR 15,527/2019. Ultimately, RCF were replaced by RAAC, and the possibility of using them as systems to serve two functions was evaluated. It was verified that RAAC are inefficient as a flow control structure at source, especially in relation to overflow volume and more frequent precipitations; however, RCF and RAAC had similar behavior when subjected to greater intensity precipitation events.